Turmeric powder in the diet of Japanese quails improves the quality of stored eggs - GUIMARÃES,Rívia Ribeiro (2021)
SUMMARY This study evaluated the effect of turmeric powder (TP) on the productivity and egg quality of quails and on the quality of eggs stored at different temperatures for 7 or 14 d. Quails were distributed in three treatments that consisted of sorghum-based diets with 1.5% and 3% TP or zero TP inclusion, with five replicates for 84 d. Eggs were stored at ambient temperature or refrigerated for 7 or 14 d in a 3 × 2 × 2 factorial arrangement with three TP levels × two storage temperatures (ST) × two storage periods (SP). Inclusion of TP did not affect the performance of the quails or egg quality at 84 d. Interaction SP × ST influenced the height and diameter of yolk and albumen, and the Haugh unit value. Eggs of quails with a diet supplemented with 3% TP and stored for 14 d showed specific gravity similar to the eggs stored for 7 d, despite the TP supplementation. It was concluded that diets with 3% TP did not affect the performance and quality of fresh eggs but improved the quality of eggs stored for 14 d at ambient temperature.